Meningkatkan Kosakata Bahasa Inggris Taruna Poltekbang Surabaya Melalui Strategi Ide Utama dan Strategi Meringkas - Laila Rochmawati (Jurnal Penelitian)
One of the main pillars in language education and as the core of a major language expertises. English in the world of aviation is vocabulary. This scrutiny works to influence the consequence of the implementation of the main inspiration strategy and the summarization strategy on the English vocabulary education of the Surabaya Poltekbang cadets. Comprehension deficiency of the vocabulary of the Surabaya Poltekbang cadets causes the cadets to experience innumerable difficulty in using English, which affects their language skills (reading, writing, observing and having dialogue). Taking non-random illustrations, 48 ​​cadets with the Surabaya aviation polytechnic. Entrants were stipulate to the experimental group (n = 24) and the control (n = 24). Vocabulary test as a pra uji and pasca uji given to entire entrants. Descriptive and inferential statistical analysis information using the SPSS application. The contrivances show that the enforcement of the main inspiration strategy and the summarization strategy as a strategy to improve knowledge of English vocabulary is not only useful in the conceptual process and description of cadets for creating, mastering and mastering the significance of vocabulary but also for putting and internalizing it in their reflections over effectively.